Relasi Sosial Pada Pelaku Phone Snubbing (Phubbing) Mahasiswa Universitas Sriwijaya Di Kota Palembang - Salsabila, Miranda Dyah; Sartika, Diana Dewi; Randi, Randi; Hendarso, Yoyok (Jayapangus Press, 2024)
The use of smartphones is very beneficial for students to learn new things and share information, but they are also unaware of the impact that the situation can have. The impact of phubbing is very important to understand because it can interfere with relationships with family, friends, and even romantic relationships. Phone snubbing or abbreviated as phubbing is a situation where a person ignores the people around him because his attention is more focused on the smartphone he is holding, which makes them not care about what is happening around them. If this behavior of phubbing is allowed, social relations between individuals will decrease because it can interfere with the individual's ability to be present and involved with people. This research aims to describe and gain an understanding of phubbing and social relations in the lives of Sriwijaya University students towards their parents and friends in the city of Palembang. Using the theory of symbolic interactionism by Mead. The research method used is the descriptive qualitative research method. Retrieval of informants using purposive techniques. Data collection techniques are carried out by observation, interviews, and documentation. The results showed that phubbing was very influential in the process of interaction between students and their parents because it resulted in disputes with their parents and friends, which was caused by phubbing because there was no mutual harmony when interacting. So that it can cause a decrease in the quality of communication and student relationships with their parents and friends.